2020
DOI: 10.2196/16656
|View full text |Cite
|
Sign up to set email alerts
|

Patient Work and Their Contexts: Scoping Review

Abstract: Background Having patients self-manage their health conditions is a widely promoted concept, but many patients struggle to practice it effectively. Moreover, few studies have analyzed the nature of work required from patients and how such work fits into the context of their daily life. Objective This study aimed to review the characteristics of patient work in adult patients. Patient work refers to tasks that health conditions impose on patients (eg, ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 108 publications
(262 reference statements)
0
26
0
Order By: Relevance
“…Table 2 outlines the nine phases in the Chronic Illness Trajectory Model, their definitions [ 16 ], and example quotes from our cohort. Table 3 lists the patient work tasks involved in each phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 outlines the nine phases in the Chronic Illness Trajectory Model, their definitions [ 16 ], and example quotes from our cohort. Table 3 lists the patient work tasks involved in each phase.…”
Section: Resultsmentioning
confidence: 99%
“…More quotes supporting each of the phases can be found in Multimedia Appendix 2 . Details of patient work tasks can be found in our previous review [ 16 ], which outlines the different task categories, how the categories were defined and created, and what examples were available for each category.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the extent to which existing care models align with the concepts of MDM [ 26 ]; where they have, with the exception of this report, they have found little alignment [ 29 ]. From the perspective of patients and healthcare professionals, the examined model of care seems to overcome specific issues identified as challenging to patients’ workload-capacity balance [ 9 ]. For example, past research has identified clinic-level factors preventing adherence and retention in care such as trouble getting appointments, lack of communication amongst clinicians, uncaring clinical teams, and inability to customize patient care plans to fit their lives [ 16 , 19 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, supporting capacity may help overwhelmed patients experience better outcomes [ 7 ]. The evidence-based work of CuCoM supported the framework of MDM care model as one that pursues patient goals while minimizing the footprint/impact of healthcare with attention to capacity and workload, which is particularly important for patients with complex or chronic conditions [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%